سبل الاستفادة من مخلفات الإنتاج النباتي، وآثارها الاقتصادية في محافظة اللاذقية - نعامه صفاء مالك; صقر إبراهيم حمدان (Latakia University Journal -Biological Sciences Series, 2014)
تم إجراء هذا البحث في محافظة اللاذقية خلال العام 2012، وهدف إلى التعرف على الواقع الراهن لمخلفات الإنتاج والتصنيع الزراعي النباتي في المحافظة، وعرض أهم الأساليب الحديثة للاستفادة منها ورفع قيمتها الغذائية. وقد بينت النتائج أن معظم المخلفات الزراعية الناتجة لا يتم الاستفادة منها بالشكل الأمثل، بل يتم رميها وتراكمها، مما يسبب هدر كميات كبيرة منها، وتلويثها للبيئة. حيث كان متوسط نسبة الإستثمار75% لمخلفات البقوليات، و65% لمخلفات الخضراوات، و 60 لمخلفات النجيليات، و 40% لمخلفات الأشجار المثمرة. كما بينت نتائج البحث أن الاستخدام الأمثل لمخلف الشعير يؤدي الى إيجاد مصدر رخيص الثمن لوحدات البروتين اللازمة للحيوان، حيث أن تكلفة الوحدة الواحدة من البروتين المهضوم الناتج عن معاملة الأتبان باليوريا تبلغ /0.5/ ل.س، وهي تمثل 1/5 من كلفة وحدة البروتين المهضوم الناتج عن استخدام الشعير كعلف. وقد حقق استخدام تبن القمح في زراعة الفطر المحاري، نتائج اقتصادية مهمة حيث قدر صافي الربح الناتج من زراعة مساحة 10م2 من الفطر المحاري باستخدام 30 كغ من تبن القمح ، بنحو 81000 ل.س. وبينت النتائج أيضاً أهمية المخلفات الزراعية في إنتاج الغاز الحيوي والسماد الناتج عنه، والذي حقق زيادة في إنتاجية محصول الذرة الشامية بنسبة 35.7%، والقمح12.5 % وتبن الحبوب 20%، والفول البلدي بنسبة 6.6%، والخضار مابين 20.6 -14.1%. This research was conducted in Lattakia province during the year 2012 first, to identify the current status of the production residues and agro-processing materials in the province and, second, to introduce modern methods of taking advantage of them and raising their nutritional value. Results showed that, the most agricultural residues are not optimally used, instead, they were disposed and accumulated causing substantial losses and environmental pollution. Results showed that, the investment average ratio of legume, vegetables, cereals, and fruit trees were 75%, 65%, 60% and 40% consensually This research conclusion shows that, the optimal use of barley residue is a source of cheap protein units that are necessary for animals feeds; where the cost per unit of digested protein resulting from urea treated hays amounts to 0.5 S.Y.P. This amount represents one fifth of the cost of protein unit from barley. Also, the use of wheat straw in the cultivation of oyster mushrooms achieve significant economic results, the net profit resulting from the cultivation area of ​​10 m2 of oyster mushrooms using 30 kg of wheat straw was about 81000 S.P. In addition to that, the research results show the importance of agricultural waste in biogas production and the resulting compost, which in turn has achieved excellent results when fertilizing crops with it. The increase in the yield of maize, wheat, faba bean and vegetables were 35.7%, 12.5%. 6.6% and 14.1-20.6% consensually.